Hiring of the Anti-Quorum Sensing Activities of Hypoglycemic Agent Linagliptin to Alleviate the Pseudomonas aeruginosa Pathogenesis - Maan T. Khayat; Tarek S. Ibrahim; Khaled M. Darwish; Ahdab N. Khayyat; Majed Alharbi; El-Sayed Khafagy; Mohamed A. M. Ali; Wael A. H. Hegazy; Hisham A. Abbas (Microorganisms, 2022)
Bacteria communicate with each other using quorum sensing (QS) which works in an inducer/receptor manner. QS plays the main role in orchestrating diverse bacterial virulence factors. Pseudomonas aeruginosa is one of the most clinically important bacterial pathogens that can cause infection in almost all body tissues. Besides its efficient capability to develop resistance to different antibiotics, P. aeruginosa acquires a huge arsenal of virulence factors that are controlled mainly by QS. Challenging QS with FDA-approved drugs and natural products was proposed as a promising approach to mitigate bacterial virulence enabling the host immunity to complete the eradication of bacterial infection. The present study aims to evaluate the dipeptidase inhibitor-4 inhibitor hypoglycemic linagliptin anti-QS and anti-virulence activities against P. aeruginosa in vitro, in vivo, and in silico. The current results revealed the significant ability to diminish the production of protease and pyocyanin, motility, and biofilm formation in P. aeruginosa. Furthermore, the histopathological examination of liver and kidney tissues of mice injected with linagliptin-treated bacteria showed an obvious reduction of pathogenesis. Linagliptin downregulation to QS-encoding genes, besides the virtual ability to interact with QS receptors, indicates its anti-QS activities. In conclusion, linagliptin is a promising anti-virulence and anti-QS candidate that can be used solely or in combination with traditional antimicrobial agents in the treatment of P. aeruginosa aggressive infections.